Should China join the GPEDC? The prospects for China and the Global Partnership for Effective Development Co-operation - Xiaoyun Li (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The Global Partnership for Effective Development Co-operation (GPEDC) is regarded as being the 21st-century epitome of a partnership within a polycentric world in the arena of international development cooperation. This discussion paper highlights the debate on the role of the GPEDC and assesses this debate by reviewing the historical process of the Development Assistance Committee (DAC)-based development cooperation (in which the GPEDC is embedded) from a non-DAC member perspective. The paper argues that the GPEDC is considered to be just another form of the DAC's transformation. That is why the emerging powers are sceptical – they are not a part of it; hence, they are reluctant to join it, or are even inclined to reject it. However, the paper also takes the realistic approach that the GPEDC is a valuable platform for continuing the role of development cooperation for global development, in particular to spearhead reforms in the international development cooperation regime and contribute to implementing the 2030 Agenda and the Sustainable Development Goals. The paper suggests how different stakeholders – including the emerging ones, particularly China – can work together to make the GPEDC a genuine partnership.
Keywords: 330